Fostering cross-program learning and experience sharing: Key take-aways from a recent Africa RISING Program exchange - Mekonnen, Kindu; Odhong, Jonathan; Ofori-Duah, Wilhelmina (International Institute of Tropical Agriculture, 2019)
Themed exchange visits to strategically selected project sites have been used over the years within Africa RISING program as a method for promoting cross-learning and experience sharing among partners that are implementing activities through the program in different countries. On 17 – 21 June 2019, activity sites in northern Ghana played host to a delegation of 40 project partners drawn from each of the 3 regional Africa RISING projects in East and Southern Africa, West Africa and the Ethiopian Highlands. This photo report captures some observations, lessons learnt, and individual reflections emanating from partners who took part in the exchange visit.